2000
DOI: 10.1203/00006450-200005000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor and Flk-1 in Developing and Glucocorticoid-Treated Mouse Lung

Abstract: Although the endothelial cell is the most abundant cell type in the differentiated lung, little is known about regulation of lung developmental vasculogenesis. Vascular endothelial growth factor (VEGF) is an endothelial cell mitogen and angiogenic factor that has putative roles in vascular development. Mitogenic actions of VEGF are mediated by the tyrosine kinase receptor KDR/murine homologue fetal liver kinase Flk-1. HLF (hypoxia-inducible factor-like factor) is a transcription factor that increases VEGF gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 35 publications
6
87
0
14
Order By: Relevance
“…Os glicocorticóides alteram a expressão do VEGF e do receptor Flk-1 no período pós-natal em pulmões de fetos normais sendo que in vivo a Dex estimula a produção de ambos e in vitro há supressão dos mesmos com Dex. Nessa fase de maturação, a proliferação endotelial é baixa sugerindo outras funções do VEGF e seus receptores na cascata do desenvolvimento pulmonar 20 . O mecanismo pelo qual a corticoterapia age sobre a produção do VEGF e de seus receptores não está completamente elucidado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os glicocorticóides alteram a expressão do VEGF e do receptor Flk-1 no período pós-natal em pulmões de fetos normais sendo que in vivo a Dex estimula a produção de ambos e in vitro há supressão dos mesmos com Dex. Nessa fase de maturação, a proliferação endotelial é baixa sugerindo outras funções do VEGF e seus receptores na cascata do desenvolvimento pulmonar 20 . O mecanismo pelo qual a corticoterapia age sobre a produção do VEGF e de seus receptores não está completamente elucidado.…”
Section: Discussionunclassified
“…Esta relação foi confirmada no presente estudo, onde as alterações do VEGFR-2 e dos pneumócitos II ocorriam concomitantemente. O VEGF induz rapidamente a conversão do glicogênio do pneumócito II em surfactante e essa ação parece ser mediada principalmente pelo FlK-1 que também sofre ação do glicocorticóide 6,20 . O VEGFR-2(Flk-1) é expresso nas fases inicias do desenvolvimento pulmonar, enquanto o VEGFR-1(Flt-1) aumenta nas fases tardias desse desenvolvimento.…”
Section: Discussionunclassified
“…In a murine model, Bhatt et al (Bhatt et al, 2000) observed that VEGF mRNA levels increased three-fold during the first two weeks of postnatal age: i.e., the alveolarization phase and expansion of the microvasculature; VEGFR-2 mRNA increased in parallel. In those studies, performed by in situ hybridization, the authors demonstrated that VEGF mRNA was mainly located in the epithelial cells of the distal air spaces.…”
Section: The Role Of Vegf In Lung Developmentmentioning
confidence: 99%
“…Conversely, a study in mice conducted by Bhatt et al (Bhatt et al, 2000), who administered dexamethasone (0.1-5 mg/ Kg/ day) from postnatal day 6 to 9, analyzed VEGF mRNA and VEGFR-2 mRNA levels in lungs, and found that VEGF and VEGFR-2 increased with increasing doses of dexamethasone. They also analyzed the effects of dexamethasone on the amount of mRNA HLF, which has been associated with an increased transcription of VEGF in normoxia and hypoxia.…”
Section: Effects Of Betamethasone Vs Dexamethasone On the Expression mentioning
confidence: 99%
See 1 more Smart Citation